The Predictive Role of Childhood Trauma and Automatic Thoughts in Cognitive Emotion Regulation of University Students - Sarıcı, HASAN; Tagay, Özlem (Pamukkale Üniversitesi, 2020)
The aim of this research is to investigate the predictive role of childhood traumatic experiences and automatic thoughts on university students’ cognitive emotion regulation. The study group of this research consists of 652 university students who study at Zonguldak Bülent Ecevit University in the 2017-2018 academic year. Research data was collected via Cognitive Emotion Regulation Scale which is developed by Onat and Otrar (2010), Childhood Traumatic Experiences Scale Short Form which is developed by Kaya (2014) and Automatic Thoughts Scale which is developed by Aydın and Aydın (2009). In data analysis, IBM SPSS and IBM AMOS programs were used. Percentage, frequency, arithmetic mean, standard deviation, and regression analysis were used in the analysis of obtained data. As a result of the analyzes, it was concluded that childhood traumatic experiences and automatic thoughts are significant predictors of cognitive emotion regulation

Bu araştırmada, üniversite öğrencilerinin bilişsel duygu düzenlemelerinde çocukluk örselenme yaşantılarının ve otomatik düşüncelerinin yordayıcı rolünü incelemek amaçlanmıştır. Araştırmanın çalışma grubunu 2017-2018 eğitim öğretim yılında farklı fakültelerde öğrenim gören 652 üniversite öğrencisi oluşturmaktadır. Araştırmanın verileri, Onat ve Otrar (2010), tarafından Türkçe’ye uyarlanan “Bilişsel Duygu Düzenleme Ölçeği”, Kaya (2014), tarafından Türkçe’ye uyarlanan “Çocukluk Dönemi Örselenme Yaşantıları Ölçeği Kısa Formu”, Aydın ve Aydın (1990), tarafından Türkçe’ye uyarlanan “Otomatik Düşünceler Ölçeği ile toplanmıştır. Verilerin analizinde, IBM SPSS ve AMOS programları kullanılmıştır. Elde dilen verilerin analizinde yüzde, frekans, aritmetik ortalama, standart sapma, ve regresyon analizi kullanılmıştır. Yapılan analizler sonucunda, çocukluk örselenme yaşantılarının ve otomatik düşüncelerin bilişsel duygu düzenlemenin anlamlı birer yordayıcıları olduğu sonucuna varılmıştır.
Üniversite Öğrencilerinin Bilişsel Duygu Düzenlemelerinde Çocukluk Örselenmeleri ve Otomatik Düşüncelerin Yordayıcı Rolü